Islamic Law and Its Role in Regulating Contemporary Society - Syaiful Ma'ruf; Tamir Moustafa (Edujavare Publishing, 2026)
This study analyzes the role of Islamic law in regulating contemporary society. The research aims to examine how Islamic legal principles are applied in modern social, economic, and legal systems and how they contribute to justice, welfare, and social order. A normative legal research method is used with conceptual and doctrinal approaches, based on secondary data from Islamic legal texts, academic literature, and institutional reports. The findings show that Islamic law regulates contemporary society through principles of justice, welfare, and ethical responsibility, supported by mechanisms such as Islamic finance, family law, and social welfare instruments. However, challenges such as differing interpretations, globalization, and legal pluralism affect its implementation. The study concludes that Islamic law remains a relevant and dynamic legal system capable of addressing contemporary societal needs when supported by strong institutional and scholarly frameworks.